Ancient Philosophy and Early Christianity : Studies in Honor of Johan C. Thom - Kotzé, Gideon R. (Novum Testamentum, Supplements, 2022)
This volume celebrates the scholarship of Professor Johan C. Thom by tackling various important topics relevant for the study of the New Testament, such as the intellectual environment of early Christianity, especially Greek, Latin, and early Jewish texts, New Testament apocrypha and other early Christian writings, as well as Greek grammar. The authors offer fresh insights on philosophical texts and traditions, the cultural repertoire of early Christian literature, critical editions, linguistics and interpretation, and comparative analyses of ancient writings.